Bimbingan Konseling Islam dalam Mengatasi Stres Akademik Peserta Didik Selama Pandemi Covid-19 - Septian Kurnia Sari; Efi Tri Astuti (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2022)
This study aims to analyze how Islamic counseling guidance deals with student academic stress during the Covid 19 pandemic. Corona Virus Disease 19 or commonly referred to as Covid 19 has affected every line of life without exception in the field of education. The method used in this study is research literature based on scientific articles, books and reports related to the research topic. The results showed that there were several factors behind the occurrence of academic stress in students. Islamic counseling guidance is intended to strengthen the religious nature of students. If a teacher, especially a PAI teacher, has the skills and is able to implement aspects of monotheism, moral aspects, aspects of worship, personal aspects, social aspects and academic aspects of Islamic Counseling Guidance to their students, then the academic stress that is motivated by the problems caused by the Covid 19 pandemic that has caused analyzed from several journals will be resolved slowly. Islamic Counseling Guidance can foster the mental health of students, form a positive personality in accordance with the guidance of the Qur'an and Hadith.